(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
the article outlines the peculiarities of information and analysis activities carried out in the internal affairs bodies and important aspects of systematic thinking and systematic analysis in the functioning of the information and analysis system in it, and describes important aspects of the preparation of a reference in the information and analytical process, relying on practice experiments.